2021
DOI: 10.1002/cpt.2246
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the CYP2D6 Haplotype Activity Scores Based on Metabolic Ratios of 4,700 Patients Treated With Three Different CYP2D6 Substrates

Abstract: The metabolic activity of the polymorphic CYP2D6 enzyme is dependent on the CYP2D6 genotype; however, the guidelines for translating the genotype into phenotype, which are of relevance for adequate drug dose personalization, are ambiguous. In the present study, retrospective therapeutic drug monitoring data from 4,700 CYP2D6 genotyped patients treated with risperidone, venlafaxine, and/or aripiprazole were analyzed to quantify the effect of CYP2D6 genotype on the CYP2D6 metabolic activities, as measured by met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 13 publications
(19 reference statements)
0
32
0
1
Order By: Relevance
“…Patients can be classified into CYP2D6 ultrarapid metabolizers (UMs), normal metabolizers (NMs), intermediate metabolizers (IMs), and poor metabolizers (PMs). 3 The CYP2D6 IM group is heterogeneous and can be divided into two subcategories, based on having relatively higher (CYP2D6 IM+) and lower (CYP2D6 IM-) enzyme activity. 4 Knowledge of the CYP2D6 genotype can be utilized for prediction of drug metabolism in vivo.…”
Section: The Polymorphic Nuclear Factor Nfib Regulates Hepatic Cyp2d6...mentioning
confidence: 99%
See 1 more Smart Citation
“…Patients can be classified into CYP2D6 ultrarapid metabolizers (UMs), normal metabolizers (NMs), intermediate metabolizers (IMs), and poor metabolizers (PMs). 3 The CYP2D6 IM group is heterogeneous and can be divided into two subcategories, based on having relatively higher (CYP2D6 IM+) and lower (CYP2D6 IM-) enzyme activity. 4 Knowledge of the CYP2D6 genotype can be utilized for prediction of drug metabolism in vivo.…”
Section: The Polymorphic Nuclear Factor Nfib Regulates Hepatic Cyp2d6...mentioning
confidence: 99%
“…The CYP2D6 metabolic capacity in vivo is predominantly genetically determined. Patients can be classified into CYP2D6 ultrarapid metabolizers (UMs), normal metabolizers (NMs), intermediate metabolizers (IMs), and poor metabolizers (PMs) 3 . The CYP2D6 IM group is heterogeneous and can be divided into two subcategories, based on having relatively higher (CYP2D6 IM+) and lower (CYP2D6 IM‐) enzyme activity 4 …”
mentioning
confidence: 99%
“…reported that “taking the enhancer SNP into account when assigning AS with the CYP2D6*2 allele led to more variability being explained in CL 0 compared with conventional AS assignments” in their racially mixed study population 19 . However, this finding may also be explained, at least in part, by having “downgraded” the AS of diplotypes containing CYP2D6*2 and a *41 or *9 allele; for the latter there is mounting evidence supporting that a lower value for AS calculation may more precisely reflect their activity and will therefore likely improve phenotype prediction 35–37 …”
Section: Discussionmentioning
confidence: 99%
“…It will thus require many large studies on various CYP2D6 substrates to provide solid evidence for groups, such as the CPIC, to revise their recommendations. In this issue of Clinical Pharmacology and Therapeutics , Jukić et al 6 . provide data needed to fill some of the existing knowledge gaps.…”
Section: Figurementioning
confidence: 99%
“…Figure provides a comparison of the CPIC recommended AS for selected diplotypes and activity predicted by Jukić et al 6 . based on metabolic ratio measurements.…”
Section: Figurementioning
confidence: 99%